2010
DOI: 10.1002/bem.20641
|View full text |Cite
|
Sign up to set email alerts
|

Human keratinocytes in culture exhibit no response when exposed to short duration, low amplitude, high frequency (900 MHz) electromagnetic fields in a reverberation chamber

Abstract: We exposed normal human epidermal keratinocytes to short duration, high frequency, and low amplitude electromagnetic fields, similar to that used by mobile phone technologies. We paid particular attention to the control of the characteristics of the electromagnetic environment generated within a mode stirred reverberation chamber (statistical homogeneity and isotropy of the field and SAR distribution). Two non-thermal exposure conditions were tested on the epidermal cells: 10-min exposure with a field amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In addition, the data are very heterogeneous, making any comparison difficult. Several publications showed no significant difference between sham or exposed cells [Gurisik et al, 2006;Qutob et al, 2006;Whitehead et al, 2006a;Chauhan et al, 2007;Huang et al, 2008], or described weak changes that were not confirmed by RT-PCR validation [Zeng et al, 2006;Paparini et al, 2008;Roux et al, 2011;Sakurai et al, 2011], while other microarray studies reported modified gene expression after radiofrequency exposure [Belyaev et al, 2006;Nylund and Leszczynski, 2006;Remondini et al, 2006;Zhao et al, 2007;Huang et al, 2008]. However, these positive studies reported a small number of responsive genes (9-34) with a FC generally close to, or lower than 2.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, the data are very heterogeneous, making any comparison difficult. Several publications showed no significant difference between sham or exposed cells [Gurisik et al, 2006;Qutob et al, 2006;Whitehead et al, 2006a;Chauhan et al, 2007;Huang et al, 2008], or described weak changes that were not confirmed by RT-PCR validation [Zeng et al, 2006;Paparini et al, 2008;Roux et al, 2011;Sakurai et al, 2011], while other microarray studies reported modified gene expression after radiofrequency exposure [Belyaev et al, 2006;Nylund and Leszczynski, 2006;Remondini et al, 2006;Zhao et al, 2007;Huang et al, 2008]. However, these positive studies reported a small number of responsive genes (9-34) with a FC generally close to, or lower than 2.…”
Section: Discussionmentioning
confidence: 80%
“…Roux et al failed to find differences in gene expression of normal human keratinocytes exposed to 900 MHz, CW, for 10 min (2.6 W/kg) or 30 min (0.73 W/kg) compared to sham-exposed cultures. As a matter of fact, some genes had a different expression but this result was not confirmed by RT-PCR (Roux et al, 2010). Sakurai et al (2011) also found altered gene expression not confirmed by RT-PCR in human-derived glial cells exposed for 1, 4 or 24 h to 2450 MHz, CW, at 1, 5 or 10 W/kg SAR.…”
Section: Non Genotoxic Effectsmentioning
confidence: 95%
“…It appears therefore that in lymphoblastic leukemia cells, the 900 MHz MW-EMF may act as a double target negative regulator of genes: it affects the control of chromosomal organization and induces inhibition of angiogenesis that leads to tumor progression and metastatic transformation. It is worth mentioning that several previous microarray analyses carried out after RF exposure failed to detect any significant changes in the gene expression in normal peripheral [32] or CNS glial cells [33] or cancer cell models.…”
Section: The Effect Of Rf Exposure On In Vitro Models: Finding the Pamentioning
confidence: 99%